Analisis Modal Usaha dalam Mendukung Kinerja Usaha pada Bara Hidroponik - Febrianto, Zakharia Anggiat; Charina, Anne (Universitas Galuh, 2026)
Business performance reflects the extent to which a company achieves its objectives. However, in practice, many business actors face various challenges that hinder performance achievement, including Bara Hidroponik.The purpose of this study is to analyze the role of financial, social, and human capital in supporting the performance of hydroponic businesses both in financial and non-financial aspects. This study employs a qualitative approach using a case study design at Bara Hidroponik, with data collected through in depth interviews involving the business owner, operational staff, partners, and consumers, as well as direct observation of operational activities. The findings show that financial capital plays a greater role in financial performance due to the capital structure being dominated by personal funds, which limits expansion. Social capital contributes more to non-financial performance as a wide business network provides access to information and collaboration opportunities. Human capital also plays a more significant role in financial and non-financial performance due to high employee competence, which drives responsive service. Future research is recommended to use a quantitative approach in order to gain a more thorough and comprehensive understanding.